Orality, Reading and Writing, Mediator Competences of the Learning of the Chemistry Curriculum: The Case of the Chemical Equilibrium - Candela Rodríguez, Boris Fernando (Rastros Rostros, 2020)
Introduction: esearchers in chemistry have considered that one of the key goals of the curriculum of this discipline, is the scientific literacy in the fundamental sense (to speak, to read and to write) and derivative sense (to understand the products and process of chemistry). Although this purpose has been a key element of the current curricular reforms of this discipline, in the teaching practice it has been difficult to achieve, teachers have focused on assisting students in the understanding of theoretical models, neglecting the development of linguistic competences of orality, reading and writing as constitutive elements of chemistry. Methodology: A qualitative methodology was used for case studies, which required the collection of data from documentary sources such as videos, field notes, narrative stories and student work. Results: this research allowed us to see that to achieve the desired literacy in the chemistry classroom, the teacher is required to consciously assist his students in the integrated development of the speaking, reading and writing language skills of and about chemistry, within a sociocultural context. Conclusion: the teaching of the different contents of the chemistry curriculum in secondary school should be mediated by the synergistic development of linguistic skills such as orality, reading and writing within an experimental or phenomenological context.